1999
DOI: 10.1034/j.1600-0412.1999.780905.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of betamethasone on fetal biophysical activities and Doppler velocimetry of umbilical and middle cerebral arteries

Abstract: Betamethasone induces a profound, albeit transient, suppression of fetal breathing, limb and trunk movements, resulting in decreased biophysical profile scores. Awareness of this drug-induced effect might prevent unnecessary iatrogenic delivery of preterm fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 15 publications
2
10
0
2
Order By: Relevance
“…Several studies have investigated the effect of betamethasone on Doppler parameters of the MCA and found decreased or unchanged MCA PI levels in different patient groups. In some of these studies, a PI decrease was observed in both complicated pregnancies and those pregnancies that already had a high MCA PI before betamethasone administration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the effect of betamethasone on Doppler parameters of the MCA and found decreased or unchanged MCA PI levels in different patient groups. In some of these studies, a PI decrease was observed in both complicated pregnancies and those pregnancies that already had a high MCA PI before betamethasone administration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using ultrasound Doppler flowmetry to examine glucocorticoid effects on CBF in human fetuses have yielded controversial results. Initial studies reported that the pulsatility index in the middle cerebral artery remained unchanged 48 h and 96 h after dexamethasone administration (Rotmensch et al 1999) as well as 24 and 72 h after a second dose of betamethasone (Cohlen et al 1996). Conversely, a recent study found a significant decrease in the pulsatility index in the middle cerebral artery 24 h after betamethasone treatment (Edwards et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Data from fetuses at risk for preterm delivery without IUGR or placental dysfunction suggest that there are no changes in umbilical artery pulsatility index (UA‐PI) after antenatal glucocorticoids3–7. A decrease in middle cerebral artery PI (MCA‐PI) has been reported in two studies5, 6, but in three other studies no change in MCA‐PI was found after antenatal glucocorticoid administration3, 4, 7.…”
Section: Introductionmentioning
confidence: 99%
“…Data from fetuses at risk for preterm delivery without IUGR or placental dysfunction suggest that there are no changes in umbilical artery pulsatility index (UA‐PI) after antenatal glucocorticoids3–7. A decrease in middle cerebral artery PI (MCA‐PI) has been reported in two studies5, 6, but in three other studies no change in MCA‐PI was found after antenatal glucocorticoid administration3, 4, 7. In IUGR fetuses or fetuses with signs of placental dysfunction, return of the end‐diastolic velocities in the UA has been reported following the antenatal administration of glucocorticoids8, 9; however, in two other studies no effect on UA‐PI was observed10, 11.…”
Section: Introductionmentioning
confidence: 99%